2017
DOI: 10.1590/s0100-204x2017000700009
|View full text |Cite
|
Sign up to set email alerts
|

Productive and reproductive performances of Santa Inês ewes fed diets supplemented with protected fat in the postpartum

Abstract: -The objective of this work was to evaluate the effect of the inclusion of protected fat in the concentrate on the productive and reproductive performances of Santa Inês ewes in feedlot, up to 60 days after parturition. Thirty-six pregnant Santa Inês ewes, with an average age of 24 months and initial weight of 46.54±7.87 kg, were used. A completely randomized experimental design was used, with three treatments: CS, concentrated supplement; G5, concentrated supplement with 5.5% protected fat (PF); and G10, conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Similarly, Espinosa, López-Molina, Ramírez-Godínez, Jiménez and Flores (1998) evaluated the effect of protected fat on the feeding of lactating sheep and didn't observe any difference in lamb performance. Moreover, Bona et al (1994) worked calcium salts from fatty acids at different levels in postpartum sheep and their offspring and verified no difference (P>0.05) for the average daily gain. These results corroborate those described by Costa et al (2011), who observed that Santa Inês lambs from ewes supplemented with protected fat didn't obtain differentiation in performance when compared to lambs from sheep that didn't receive fat.…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, Espinosa, López-Molina, Ramírez-Godínez, Jiménez and Flores (1998) evaluated the effect of protected fat on the feeding of lactating sheep and didn't observe any difference in lamb performance. Moreover, Bona et al (1994) worked calcium salts from fatty acids at different levels in postpartum sheep and their offspring and verified no difference (P>0.05) for the average daily gain. These results corroborate those described by Costa et al (2011), who observed that Santa Inês lambs from ewes supplemented with protected fat didn't obtain differentiation in performance when compared to lambs from sheep that didn't receive fat.…”
Section: Resultsmentioning
confidence: 89%
“…In prepartum, supplementation of ADE vitamins improved energy metabolism ( 40 ). In the postpartum period, protected fat was not recommended because it reduced the probability of gestation ( 41 ). As for energy by-products, crude glycerin could be recommended for up to 10%, not affecting reproductive performance before and during the breeding season ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was a low variation in mean birth weight between treatments and lambs had a mean birth weight of 4.3 kg, which made homogeneity in both groups. The mean lamb birth weight can be classified as adequate to sheep breeding patterns and is related to the good nutritional conditions of the matrices and to the reproductive genetics (Santos et al 2017).…”
Section: Productive Performancementioning
confidence: 99%
“…At this stage, the energy balance is negative and the sheep have to meet their maintenance and milk production requirements. As a result, at the same time as food intake and nutrients are being absorbed from the gastrointestinal tract, there is also mobilization of fat and protein from the adipose and muscular tissues (Santos et al 2017). Therefore supplementation (CP = 163.9 and TDN = 812.8 g/kg BW) offered during lactation was essential to meet the nutritional requirements of the matrices, independently of the supplementation received by lambs.…”
Section: Ingestive Behaviormentioning
confidence: 99%